West African Migrants and Okada (Commercial Motorcycle) Business in Ibadan Since the 1990s (2013)
In Ibadan, Nigeria, urban dysfunction was signified by overcrowding and a chaotic transport system. The widespread use of okada (commercial motorcycle) generated income and inconveniences for urban dwellers. Due to their poor economic background, most okada (commercial motorcycle) riders were in the business to buy time and get cheap money. This paper examines the social experiences of young West African migrants who competed with unemployed (or underemployed) Nigerians in the ubiquitous okada business and illuminates the risks and ambition of young migrants in making money in the informal transport sector. Since the 1990s, okada has been a symbol everyday coping mechanisms of the struggling migrants and the urban poor to earn a living against the vagaries of harsh economic realities. The paper argues that there are confrontations over the use of urban space between state authorities and Okada riders. Banning okada invoked a new urban governance dynamics in terms of security and rebranding. Against all the risk factors, West African okada riders continue to struggle with the aspirations of making money.